Simultaneous Extraction and Determination of Compounds With Different Polarities From Platycladi Cacumen by AQ C18-Based Vortex-Homogenized Matrix Solid-Phase Dispersion With Ionic Liquid - Ding, Mingya; Li, Jin; Zou, Shuhan; Tang, Ge; Gao, Xiumei; Chang, Yan-xu (Frontiers in Pharmacology, 2019)
This study presented a rapid, simple and environmentally-friendly method of employing AQ C18-based vortex-homogenized matrix solid-phase dispersion with ionic liquid (AQ C18-IL-VHMSPD) for the extraction of compounds with different polarities from Platycladi cacumen (PC) samples by ultra high-performance liquid chromatography with PDA detection. AQ C18 (aqua C18) and ionic liquid ([Bmim]BF4) were used as the adsorbent and green elution reagent in vortex-homogenized MSPD procedure. The AQ C18-IL-VHMSPD conditions were optimized by studying several experimental parameters including the type of ionic liquid, the type of adsorbent, ratio of sample to adsorbent, the concentration and volume of ionic liquid, grinding time and vortex time. The recoveries of the target compounds were in the range of 96.9%-104% with relative standard deviation values no more than 2.8%. The limits of detection and limits of quantitation were in the range of 0.2-1.2 ng mL-1 and 1.0-5.4 ng mL-1, respectively. Compared with the traditional ultrasonic-assisted extraction, the developed AQ C18-IL-VHMSPD method required less sample, reagent and time. It was concluded that the AQ C18-IL-VHMSPD method was powerful method for the extraction and quantification of the high polarity and low polarity compounds in traditional Chinese medicines samples.